Relationship Between Diet Patterns and Hypertension Levels in the Elderly - Nur Nunu Prihantini; Avidya Ihromi; Nolly O. H. Rantung (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hypertension is a common health problem in the elderly population and is a significant risk factor for cardiovascular diseases. Dietary patterns are known to influence blood pressure control significantly, yet many elderly individuals continue to follow unhealthy eating habits that may exacerbate their condition. Objective: This study aims to determine the relationship between dietary patterns and hypertension levels in elderly individuals. Aims: This study aims to explore the relationship between dietary patterns and hypertension levels in the elderly and to analyze the distribution of hypertension based on age group and severity. Methods: This study used a quantitative approach with a cross-sectional observational analytical design. Data were collected from 45 elderly respondents through interviews using a structured dietary questionnaire and direct blood pressure measurement using a calibrated digital sphygmomanometer. Data analysis was conducted in two stages: univariate analysis to describe the characteristics of respondents and the distribution of hypertension, and bivariate analysis using the Chi-square test to assess the relationship between dietary patterns and hypertension levels. Results: The results showed that most respondents came from the 60-69 age group (88.89%), and the 70-79 age group (11.11%). Most respondents (57.8%) experienced stage I hypertension, while the rest (42.2%) experienced stage II hypertension. Bivariate analysis showed a significant relationship between diet and hypertension levels (p-value = 0.035). Respondents with a good diet tended to experience stage I hypertension (77.8%), while a poor diet was more dominant in stage II hypertension (78.9%). Conclusion: This study shows a significant relationship between diet and hypertension levels in the elderly in Bekasi City. The elderly with a good diet tend to experience stage I hypertension, while a poor diet correlates with stage II hypertension. These results indicate that diet plays an important role in the severity of hypertension in the elderly.